Principal's Strategy to Improve Continuous Learning Competencies for Teachers in Responding to Educational Challenges in the 21st Century - Sholikhah, Khotimatus; Harun Rasyid, Mahmutarom; Retno Ekaningrum, Ifada (Journal of Neonatal Surgery, 2025)
The challenges of education in the 21st century is increasingly complicated, characterized by complexity, chaos, fierce competition, and change. This makes it a challenge for school principals. School principals must be able to answer this challenge if they want superior and competitive human resources. Teachers' participation in continuous learning activities can encourage teachers to develop their profession optimally. This study aims to identify the strategies of school principals at the junior high school (SMP) level in Lamongan Regency in improving teachers' continuous learning competencies to face the challenges of 21st century education. The research method used in this study is a mix method with the design of an exploratory sequestrian mixed research method. The results of the study explain the strategy carried out by junior high school principals in Lamongan Regency to improve continuous learning competencies through supporting sustainable development programs, providing access to technology as a learning resource for teachers and students, creating a learning culture, implementing supervision and motivating teachers through award programs.